Identification of Maternal Risk Factor with Preterm LBW Babies in a Tertiary Care Hospital (TAJ: Journal of Teachers Association, 2018)
This study was aimed to identify risk factors of preterm LBW babies by following a cross sectional type of comparative study. This study was conducted at inpatient department of paediatrics of Rajshahi Medical College Hospital from January 2009 to December 2010. A total 150 preterm babies were included in this study. The mothers of the babies were studied to identify some selected risk factors. Maternal poor nutritional status (p